Einige Extremaleigenschaften der Funktionen, die keine nullgleiche dividierte Differenz haben - Kirjackis, E. (Lithuanian Mathematical Journal, 1970)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:Э. Г. Кирьяцкий. Некоторые экстремальные свойства функций с отличной от нуля разделенной разностьюE. Kirjackis. Funkcijų, kurių padalytas skirtumas nelygus nuliui, kai kurios ekstremalinės savybės